A rare case of median arcuate ligament syndrome presenting with chronic abdominal pain managed surgically: A case report - Md. Deluwar Hussen, MBBS; Zareen Tabassum, MBBS; Anawara Afroz Jenny, MBBS; Kashfia Naharin, MBBS; Farjana khanam, MBBS (Radiology Case Reports)
The disorder median arcuate ligament syndrome (MALS) develops when the median arcuate ligament compresses the celiac artery and accompanying nerve fibers leading to postprandial abdominal pain, nausea and bloating symptoms that are commonly mistaken for other gastrointestinal or vascular conditions. A 29-year-old female patient experienced right hypochondrium pain after eating combined with burning stomach pain and debilitating bloating episodes for 5 months. Computed tomography (CT) angiography scan and Doppler ultrasonography revealed celiac artery stenosis due to pressure from the median arcuate ligament along with cholelithiasis. The patient's vague symptoms illustrate the diagnostic difficulty of MALS patients who also have cholelithiasis and demonstrates how CT and Doppler ultrasonography serve crucially to validate MALS diagnosis. Surgical treatment of the median arcuate ligament by physical release has proved successful in treating symptoms despite patients also having cholelithiasis. Early detection and surgical treatment can increase favorable outcomes for patients with such rare conditions.